Network models development and community detection in identifying similar socioeconomic profiles - Porto, Rodrigo de A.; Frinhani, Rafael de M. D.; Mendes, Felipe R. M.; Souza, Vanessa C. O. De (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe), 2025)
The growing demand for scholarships in higher education and the limited financial resources make it challenging to select candidates with the most significant socioeconomic vulnerability. To assist in this task, we developed three graph-based models to represent the network of candidates for student aid. We applied the Community Detection methods Fast Greedy, Multilevel, and Walktrap to the networks generated by each model to identify groups of candidates with the most significant similarity in socioeconomic characteristics. Computational experiments were performed with real data from three years of aid applications from a Brazilian federal university to validate the models. We analyzed the generated solutions for cohesion and external isolation between communities based on metrics such as modularity and the number of edges between communities. Model 2 (Multirelational) obtained the best results in the three datasets analyzed, with the Fast Greedy method delivering more cohesive communities than the others. We noticed that the Community Detection method greatly influences the obtaining of better quality solutions, which in some cases reduced the inter-community edges by about eight times in cases with the same number of communities. The work brings contributions by presenting three network models for academic management, a context that still needs to be explored in the literature, which, together with Community Detection methods, can potentially classify data in an unsupervised manner.